Interspike intervals reveal functionally distinct cell populations in the medial entorhinal cortex - Latuske, Patrick; Toader, Oana-Daniela; Allen, Kevin (The journal of neuroscience, 2015)
The superficial layers of the medial entorhinal cortex (MEC) contain spatially selective neurons that are crucial for spatial navigation and memory. These highly specialized neurons include grid cells, border cells, head-direction cells, and irregular spatially selective cells. In addition, MEC neurons display a large variability in their spike patterns at a millisecond time scale. In this study, we analyzed spike trains of neurons in the MEC superficial layers of mice and found that these neurons can be classified into two groups based on their propensity to fire spike doublets at 125-250 Hz.